2010
DOI: 10.1016/j.jse.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical consequences of humeral component malpositioning after anatomical total shoulder arthroplasty

Abstract: Hypothesis: We hypothesized that the malpositioning of the humeral component can preclude the longterm success of anatomical total shoulder arthroplasty. The goal of this study was to evaluate the mechanical consequences of superior and inferior malpositioning of the humeral head. Materials and methods: A numerical musculoskeletal model of the shoulder joint allowing natural humeral head translation was used to simulate a loaded abduction movement controlled by muscular activation. An inferior and superior mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 24 publications
(27 reference statements)
0
27
0
Order By: Relevance
“…Multiple studies use different cut-off points to define overstuffing of the gleno-humeral joint [8, 2730, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies use different cut-off points to define overstuffing of the gleno-humeral joint [8, 2730, 32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, though minor, there is a slight error in measurements using handheld point calipers. Numerous authors have demonstrated that accurate implant placement is crucial for restoring normal glenoid kinematics and motion [5][6][7][8] and others have shown worsening clinical outcomes and higher rates of pain and implant loosening when implants were not placed anatomically. [1][2][3] This is such an important concept that it essentially was the primary inspiration for creating the implant under investigation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…performed a biomechanical analysis using a 3-dimensional numerical musculoskeletal model of the glenohumeral joint to show that even a small error in positioning of the humeral component can impact functional outcome and life-time of an anatomic TSA. 19 Inferior malpositioning of the head resulted in impingement and limited abduction, while superior malpositioning resulted in increased risk of subluxation. Both inferior and superior malpositioning caused increased stress on the cement mantle of the glenoid.…”
Section: Discussionmentioning
confidence: 99%